Food to politics: Representations of genetically modified organisms in cartoons on the Internet in China. (April 2021) - Wang, Guoyan; Wang, Lingfei; Shen, Jiafei
Controversies around genetically modified (GM) food have become particularly prevalent in China. To understand the situation, 257 GM cartoons were collected from various Chinese online sources. We found that China's GM cartoons peaked during controversial social events from the end of 2012 to 2016, which is consistent with the Baidu Media Index on GM headline news. About 85% of the cartoons involve GM food and more than half of cartoons share scary information. The mainstream media is more neutral and not only presents the dilemma in choice but also promotes genetically modified organisms (GMOs). However, social media inclines toward a more pessimistic view, providing scary information and focusing on health risks and conspiracy theories. Controversial topics have fueled the spread of political conspiracy theories. Generally, scientists supporting GMOs have been criticized under suspicion of betraying their country, and the issue of GM food in China reflects strong political views.